Intoleransi terhadap, air susu sapi (milk intolerance) - Zainal Arifin Nang Agus, Zainal Arifin Nang Agus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Cows milk has been recognised as an almost ideal food because it serves as a source of complete nutrients. Unfortunately, there are some people who cannot drink milk (milk intolerance) because lack of lactase.. High frequency of milk intolerance is found in developing or tropical countries and non-Caucasian race. It is a problem for public nutrition in those countries. Lactase is an inducible enzyme. The inductor is lactose, a major carbohydrate in milk. Some studies suggested that milk intolerance was influenced by genetic factors, diet and milk drinking habit. Efforts to overcome milk intolerance by providing low lactose milk had been done, but the result was not yet successful.Key words: protein calori malnutrition - cows milk - lactase deficiency - milk intolerance